2004
DOI: 10.1097/00005131-200410000-00003
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the A-V Impulse System in the Treatment of Posttraumatic Swelling Following Ankle Fracture

Abstract: The A-V Impulse "in-cast" system demonstrated significant benefit in the management of adults with isolated ankle fractures who could not undergo immediate open reduction and internal fixation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 16 publications
0
29
0
2
Order By: Relevance
“…We used a standardized assessment protocol to minimize the known sources of error [13]. We performed the ultrasonography studies using a Philips HDI 5000 (Philips, Bothell, WA, USA) duplex ultrasound device with a variable highfrequency linear array transducer (5)(6)(7). During the examinations, we placed the subjects in a 308-reverse Trendelenburg position with the leg externally rotated to minimize active dorsal or plantar flexion.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a standardized assessment protocol to minimize the known sources of error [13]. We performed the ultrasonography studies using a Philips HDI 5000 (Philips, Bothell, WA, USA) duplex ultrasound device with a variable highfrequency linear array transducer (5)(6)(7). During the examinations, we placed the subjects in a 308-reverse Trendelenburg position with the leg externally rotated to minimize active dorsal or plantar flexion.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies suggest the degree of increase in flow velocity is a good hemodynamic measure of device efficacy [9,24,25]. Nevertheless, clinical studies suggest patient compliance and consistent application of compression devices throughout each 24-hour period are imperative to ensure DVT prophylaxis [5,18,22]. A well-designed mechanical device should incorporate augmentation of peak venous velocity, augmentation of venous volume return, ease of device application, and patient comfort, which are essential for user compliance to ensure continuing use throughout the day.…”
Section: Introductionmentioning
confidence: 99%
“…They reported an average twenty-four-hour edema reduction of 53% preoperatively in the impulse compression group, whereas the cool pack group had a reduction of 10%. Caschman et al 18 found that the impulse compression in-cast system significantly reduced the time taken for ankle swelling to diminish prior to surgery when compared with elevation only. They also found that wound and skin complications could be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Multilayer compression bandaging has been used in our hospital with positive effects in treating edema in patients with trauma. Various publications [18][19][20][21][22][23] also suggest the use of intermittent impulse compression devices in reducing traumatic edema. These devices contain an inflatable pad that intermittently applies pressure to the plantar arch of the foot to compress the concomitant veins and lymphatic vessels of the lateral plantar artery, thereby enhancing venous backflow 24,25 .…”
mentioning
confidence: 99%
“…Caschman et al performed a prospective, randomized, controlled study to determine the efficacy of the A-V Impulse "in cast" system (Novamedix Services, Andover, United Kingdom) for the treatment of posttraumatic swelling following ankle fracture 66 . Sixty-four patients with an isolated ankle fracture were randomized to treatment with limb elevation (control group) or with an A-V Impulse bladder that was fitted under the arch of the foot within a splint for intermittent pneumatic pedal compression (study group) while awaiting surgery.…”
Section: Ankle and Footmentioning
confidence: 99%